Comparison of brainwave pattern for alpha state between smokers and non smokers after motion technology / Amyza Ibrahim - Ibrahim, Amyza (2007)
This paper presents a research project to compare the brainwave pattern for alpha state of smokers and non smokers of UiTM student with correlation to motion technology. Twenty one samples were observed before and after the motion treatment by using EEG equipment. A short interview was carried out for each respondent to confirm the results. It was found that generally motion treatment produced a significant improvement in terms of reducing the smoking habit.